Forms Of Greetings in Different Types of English Discourse - Mirzayeva Zarnigor Odilsher qizi (Zien Journals, 2024)
This article discusses the problems of greeting in Modern English. It studies forms of greetings in different types of English discourse.
Keywords: greeting; non-verbal expressions; form; discourse